The effect of internalized stigmatization on care burden in adolescent psychiatric patients and their parents - Gümüş, Funda; Kaçan, Havva (Frontiers in Psychiatry, 2023)
The purpose of this study was to determine the effect of internalized stigma perceived by adolescents with mental disorders and their families, on the burden of care on their families. The study was conducted in a descriptive and correlational desing with adolescents and their parents who applied to the child and adolescent psychiatry outpatient clinic between March 1 and June 1, 2022. A total 101 adolescents and 101 parents who met the sampling criteria and agreed to participate in the study. Only 1 parent per adolescent was included in the study. It was found that the mean age of the adolescents was 15.05 ± (1.80), 57.4% were female and 56.4% were secondary school graduates, and 26.7% of the adolescents, all of whom were unemployed, were diagnosed with a mood disorder, 50.5% had received outpatient treatment previously, and 22.8% had chronic diseases. It was found that the mean age of the parents who participated in the study was 45.53 ± (6.48), 77.1% were female and 28.7% were secondary school graduates. Also, 22.8% of the parents had a chronic disease, 28.7% had a chronic disease in their family and 32.7% had another family member in need of care, and 17.0% of the parents had received training on mental disorders previously. It was found that the parents’ total means ZBI score was 42.74 ± (11.92). When the ZBI total scores were examined in terms of sociodemographic variables, no significant differences were found between the groups according to the variables. There was only a weak, positive and significant relationship between the age of the parents and In the present study, it was found that adolescents with mental disorders and their families experienced internalized Stigmatization and this Stigmatization increased the care burden on parents. Mental health and psychiatric nurses can facilitate this population's access to treatment by planning and implementing psychosocial interventions to reduce the internalized stigma of children and adolescents and their families.